2007
DOI: 10.1111/j.1440-1835.2006.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance pattern of chloroplast DNA is correlated with gamete types based on sex‐specific arrangement of the cell fusion site in Caulerpa (Ulvophyceae, Chlorophyta)

Abstract: Using field emission scanning electron microscopy (FE-SEM) and fluorescence microscopy, the respective relationships between the arrangement of the gamete cellfusion site and the inheritance pattern of chloroplast DNA (cp-DNA) were studied for Caulerpa brachypus Harvey, C. okamurae Weber-van Bosse, C. racemosa (Forsskål) J. Agardh var. laete-virens (Montagne) Webervan Bosse, and C. serrulata (Forsskål) J. Agardh var. serrulata f. lata (Weber-van Bosse) Tseng. The eyespot of the biflagellate gamete was visualiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 65 publications
4
29
0
Order By: Relevance
“…The results also support the proposal that a sex-specific arrangement of the mating structure/cell fusion site of the gamete is a universal feature in advanced chlorophytes (Nakayama and Inouye 2000) and that it is correlated with specific mating types (Miyamura and Nagumo 2007).…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…The results also support the proposal that a sex-specific arrangement of the mating structure/cell fusion site of the gamete is a universal feature in advanced chlorophytes (Nakayama and Inouye 2000) and that it is correlated with specific mating types (Miyamura and Nagumo 2007).…”
Section: Resultssupporting
confidence: 76%
“…2f, g) was a result of sex-specific fusion. Therefore, gametes of A. caliculus are suggested to be divided into two types (type α and β) based on the cell fusion site position, as reported previously in other chlorophyte algae (Miyamura and Nagumo 2007) (Fig. 1b).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…In the flagellate gametes of green algae, fusion generally occurs at specific site of the cell. Recently, it has been found that the cell fusion sites of the gametes occupy different positions between the opposite mating types in several green algae (see Miyamura and Nagumo 2007). This was first indicated in biflagellate isogametes of chlorophycean alga Chlamydomonas reinhardtii Dangeard (Holmes andDutcher 1989, Gaffal et al 1991), in which cell fusion site is differentiated to specialized cell membrane "mating structure" (Goodenough and Weiss 1975).…”
mentioning
confidence: 99%